REPRESENTASI PENDIDIKAN SPIRITUAL ISLAM DALAM NOVEL LAUH MAHFUZ KARYA NUGROHO SUKSMANTO (PENDEKATAN FENOMENOLOGI) - Ichyaa Uluumiddin (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The purpose of this study is to describe the nature of Islamic spiritual education contained in the novel Lauh mahfuz by Nugroho Suksmanto, and to describe the Representation of Islamic spiritual education contained in the novel Lauh Mahfuz by Nugroho Suksmanto with the reality of spiritual education in the community. This study uses qualitative methods that are descriptive. That is, the reasearcher discusses and studies novels not using numbers, but emphasizes the description, which describes the novel Lauh Mahfuz. The data of this study is a novel entitled Lauh Mahfuz by Nugroho suksmanto. Data collection techniques used are documentation techniques, see techniques, and note-taking techniques in the data analysis performed. Steps: reading novels, taking data, and summarizing.The results of this study indicate that the nature of Islamic spiritual education contained in the novel Lauh Mahfuz by Nugroho suksmanto has several aspects, namely: the essence of faitheducation which and aspects of Shari'ah education which.